An Examination Of The Dimensions Of Commercialization In School Education And Its Effects On Higher Education - Ping, Li; Paramalingam, Muhantha (Journal of Neonatal Surgery, 2025)
Educational equality, accessibility, quality, and long-term results are the focus of this study, which seeks to understand the effects of privatization on K-12 and higher education. Private schools have proliferated because of school privatization, offering a better education at the expense of public schools and maybe widening income gaps. This study investigates the far-reaching consequences of privatization on the education system, specifically how it has changed the allocation of resources, the flexibility of curricula, the quality of teachers, and the growing socioeconomic performance gap. According to the research, private schools serve children from middle-class and higher-income households, while public schools have challenges due to inadequate financing, affecting the quality of education accessible to children from lower-income households. The phenomenon of access to higher education is investigated in this research, along with its development in response to the privatization and commercialization of educational institutions. Lots of people are worried about the market-driven character of schools, how much money they take from private sources, and how much tuition is going up. Researchers are looking at how modifying university curricula could affect student loan debt. More and more, the research priorities and budgets of public and private universities are diverging. The many effects of privatization are explained in this paper by analyzing data, case studies, and interviews with important players. It goes on to say that all children should have access to a good, inclusive education, and it offers policy suggestions to make that happen. The core of these suggestions is establishing a balance between the public and private sectors.